2002
DOI: 10.1046/j.1471-0528.2002.02156.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the outcome of early medical abortion: a review of 4132 consecutive cases

Abstract: Objective To assess the outcome of a regimen of a reduced dose of mifepristone followed by one or two doses of vaginal misoprostol as a non-surgical method for termination of pregnancy.Design Prospective observational study.Setting Aberdeen Royal Infirmary, Aberdeen, Scotland.Population Women seeking abortion under the 1967 Abortion Act.Methods Factors influencing the outcome in a consecutive series of 4132 women undergoing early medical abortion in one Scottish teaching hospital since 1994.Main outcome measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
40
3
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(52 citation statements)
references
References 19 publications
8
40
3
1
Order By: Relevance
“…Shorter induction abortion interval in vaginal group may be because of the long lasting and continuously increasing uterine contractility of vaginal misoprostol. 11 In both groups those with a history of previous abortion had a failure rate of 33.3% ( P=0.000 and P=0.007 respectively in oral and vaginal groups). Premila et al in a study of factors affecting outcome of early medical abortion with review of 4132 consecutive cases of have found out that those who had a previous abortion were more likely to have a failed medical abortion ( OR =2.09) 8 .…”
Section: Discussionmentioning
confidence: 91%
“…Shorter induction abortion interval in vaginal group may be because of the long lasting and continuously increasing uterine contractility of vaginal misoprostol. 11 In both groups those with a history of previous abortion had a failure rate of 33.3% ( P=0.000 and P=0.007 respectively in oral and vaginal groups). Premila et al in a study of factors affecting outcome of early medical abortion with review of 4132 consecutive cases of have found out that those who had a previous abortion were more likely to have a failed medical abortion ( OR =2.09) 8 .…”
Section: Discussionmentioning
confidence: 91%
“…[5][6][7][8] In our study, mean Induction abortion interval was 51.2 hours i.e., 3.2 hours after 800 µg misoprostol and the range was 48.5 -54 hours. This was comparable to the studies by Schaff et al and Ashok et al 4,8 The route of administration of misoprostol had no effect on the initiation of bleeding and on the induction abortion interval. The mean Induction abortion interval was longer in women with gestational age>49 days but it was not statistically significant.…”
Section: Discussionmentioning
confidence: 51%
“…This is comparable to similiar other studies. 3,8,9 There were no major side effects like infection, sepsis or maternal death. The side effects were predominantly gastrointestinal symptoms.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In 1% cases are diagnosed intact pregnancy (25,26,27,28).It cites more factors that influence the high level of failure, as the greater gestational age of 50 and 63 days, less expirience of doctors, specially in the cases of ample bleeding from uterus or strong patients` pains (27,29). If the gynecologist is trained well to recognize and set the ample bleeding, side effects and regularly explains ultrasounds findings, than the level of instrumental intervention was less.…”
Section: Mifepristone and Misoprostolementioning
confidence: 99%